109 Impact of motor vehicle crashes on long-term healthcare utilization. (5th May 2020) - Cook, Larry; Norris, Jesse; Startup, Emily; Olsenc, Cody
Abstract : Statement of Purpose: The impact of a motor vehicle crash (MVC) on health can have effects beyond injuries treated immediately following the crash. Understanding the long-term effects of an MVC can help develop programs to assist injured persons while having minimal impact on the healthcare system. Methods: We probabilistically linked MVC records from 2011 and 2015 to emergency department (ED) and hospital discharge (inpatient) records from 2010 to 2016. To assess the long-term impact of an MVC, ED and inpatient visits up to a year following the data of the crash were considered matches. ED and inpatient visits in the year preceding the crash were also linked to use as a comparison of healthcare utilization before the event. Several confounders were assessed for their impact on post-crash healthcare usage, including age, sex, injury severity, and comorbidities identified on the hospital record at the time of the crash. Results: There were 652, 486 persons involved in MVCs, of these 68, 546 (10.5%) persons linked to an ED or inpatient record associated with their MVC and comprised our study population. A higher percentage of persons had hospital treatment in the year following their crash compared to the year before [19, 568 (28.5%) vs. 16, 500 (24.1%), McNemar's p-value<0.001). Increased hospitalization usage was consistent across all ages, sexes, and comorbidities. However, post-MVC healthcare resulted in higher median charges (p<0.001) and lengths of stay (LOS) (p<0.001). This relationship increased with age where those 65–89 years had pre-MVC median charges of $3, 497 and LOS of 2 but post-MVC median charges of $4, 330 and LOS of 5 (p<0.001). Similarly, those with comorbidities experienced higher post-MVC charges ($3, 380 pre vs. $4, 362 post, p<0.001). Significance of Contributions: MVCs have an impact beyond the event itself. Those who are most fragile, such as older persons and those with comorbidities, may be differentially impacted.